Impaired salivary gland activity in patients with autoimmune polyendocrine syndrome type I - Bergithe E. Oftedal; Mihaela Cuida Marthinussen; Martina M. Erichsen; Maria K. Tveitarås; Anja Kjellesvik-Kristiansen; Daniel Hammenfors; Malin V. Jonsson; Kai Kisand; Roland Jonsson; Anette S. B. Wolff (Taylor & Francis Group, 2017)
Autoimmune polyendocrine syndrome type I (APS-I) is a severe disease caused by mutations in the autoimmune regulator (AIRE) gene. We hypothesized that salivary gland dysfunction could be a possible unexplored component of these patients and here aimed to investigate salivary and lachrymal symptoms in the Norwegian cohort of APS-I patients (N = 41) and the aetiology behind it. Sicca symptoms and possible corresponding underlying factors were assessed by subjective reports combined with objective measures of saliva and tear flow, serological testing, immune fluorescence microscopy, ultrasonography and searching for putative autoantibodies in the salivary glands. In addition, defensin and anti-defensin levels were analysed in patients and compared with healthy controls. Our results indicate mild salivary and/or lachrymal gland dysfunction manifesting in low saliva or tear flow in a total of 62% of APS-I patients. Serum IgG from 9 of 12 patients bound to targets in salivary gland biopsy slides, although the specificity and pattern of binding varied. There was no reactivity against known Sjögren-associated autoantigens in sera from APS-I patients using quantitative methods, but 11% were ANA positive by immunofluorescence microscopy. We identified several putative autoantigens in one patient, although none of these were verified as APS-I specific. We conclude that impaired salivary gland activity is part of the clinical picture of APS-I and our findings could indicate an autoimmune aetiology. We further show that APS-I patients have an altered antimicrobial signature in both sera and saliva, which requires further investigations.